2000
DOI: 10.1017/s1047951100006636
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on a respiratory ventilator due to an atrial septal defect

Abstract: An atrial septal defect is commonly thought of as a benign cardiac lesion especially in infancy. The haemodynamic consequences for the lungs, nonetheless, can be comparable to that produced by patency of the arterial duct. In a preterm boy, this lesion led to the development of broncho-pulmonary dysplasia, and dependence on a respiratory ventilator. He could be extubated shortly after surgical closure of the septal defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Of the 13 patients who underwent device closure in our series, 11 patients have improved clinically. The patients in our study with significant respiratory failure, dependency on oxygen, and poor weight gain demonstrated clinical improvement after device closure and subsequent elimination of the left to right shunt as has been previously reported 6,13 …”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Of the 13 patients who underwent device closure in our series, 11 patients have improved clinically. The patients in our study with significant respiratory failure, dependency on oxygen, and poor weight gain demonstrated clinical improvement after device closure and subsequent elimination of the left to right shunt as has been previously reported 6,13 …”
Section: Discussionsupporting
confidence: 78%
“…Systemic to pulmonary shunting with resultant increased pulmonary blood flow may lead to the eventual loss of physiologic compensation resulting in edema and endothelial injury 12 . The accumulation of interstitial fluids is aggravated by excessive administration of fluids and increased flow in the lungs due to left to right shunting 13 . In the presence of a left to right shunt, increased pulmonary blood flow might further enhance the pulmonary vascular remodeling already induced by other factors and result in pulmonary vascular obstructive disease 10,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports have found that ASOs significantly deteriorated pulmonary status [19,20]. In our study, none of the infants required intervention to close the ASO during follow-up.…”
Section: Discussionmentioning
confidence: 50%
“…[2-4] Surgical and catheter closure of such defects result in rapid respiratory improvement, with early extubation and oxygen weaning. [23] Unfortunately, this patient was referred at a later age to our center and the positive effects of early PDA ligation on the underlying respiratory status could not be assessed. It is likely that early PDA ligation in the neonatal period could have averted the chronic lung disease and the need for the procedure described herein.…”
Section: Discussionmentioning
confidence: 99%